Yoksullarla Çalışan Sosyal Hizmet Uzmanlarının Duygusal Emeği. - ACA, Zeynep (Journal of Society & Social Work / Toplum ve Sosyal Hizmet, 2021)
The present study examined the emotional labor of social workers serving the poor regarding the Emotional Labor Theory of Hochschild (1983). Based on indepth interviews, the research focused on the emotions of the social workers who always face increasing poverty and caseloads and social policy practices keeping poverty under control rather than reducing it. A total of 18 social workers selected with the snowball sampling technique were interviewed in this case study. While some of the interviews (13 interviews) were carried out face-to-face between September 20 - October 5, 2020, others (5 interviews) were conducted online. The findings revealed three interrelated aspects of the participants working with the poor: a) encountering problems in work routines frequently, b) confirmation of the adverse impacts of increasing caseloads and being always with the poor on emotional well-being and their projections on social life, and c) resorting to insensibility/depersonalization, emotional splitting, and emotional labor to deal with reactions due to constant encounters with the poor. In addition, the research findings revealed that social workers did not receive any professional emotional support.